Distinct Anti-IFI16 and Anti-GP2 Antibodies in Inflammatory Bowel Disease and Their Variation with Infliximab Therapy. Issue 12 (December 2016) - Caneparo, Valeria; Pastorelli, Luca; Pisani, Laura Francesca; Bruni, Barbara; Prodam, Flavia; Boldorini, Renzo; Roggenbuck, Dirk; Vecchi, Maurizio; Landolfo, Santo; Gariglio, Marisa; De Andrea, Marco
Abstract : Background: Inflammatory bowel disease (IBD) is characterized by a chronic inflammation of the gut, partly driven by defects in the expression and function of pattern recognition receptors, including the IFI16 protein. Because this protein is a target for autoantibodies and its aberrant expression was reported in colonic mucosa from active patients with ulcerative colitis, we studied its expression and specific seroresponse in patients with IBD before and after infliximab (IFX) therapy. Methods: Anti-IFI16 antibodies (IgG and IgA subtypes) were measured in the sera of 74 patients with IBD: 48 patients with Crohn's disease (CD) and 26 patients with ulcerative colitis, prospectively harvested before and after IFX therapy. Anti-GP2 antibodies (both IgG and IgA subtypes) were also tested for comparison. The patient antibody statuses were qualitatively and quantitatively associated with disease phenotype and response to IFX therapy. Results: Significantly higher titers of anti-IFI16 IgG were found in both CD and ulcerative colitis patients compared with healthy controls. Anti-IFI16 IgA titers were also present in patients with CD. Anti-GP2 IgG subtype titers were significantly increased in patients with CD, as were IgA subtype titers. Significant changes in anti-IFI16 IgG subtype titers were observed after IFX in patients with CD who correlated with clinical remission or response. Conclusions: Our results highlight the importance of IFI16 in IBD pathogenesis showing that its de novo overexpression in the gut epithelial cells leads to a breakdown in immune tolerance and the subsequent development of specific autoantibodies. Anti-IFI16 IgG antibodies hold the potential to serve as a biomarker of response to IFX therapy. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 15 September 2016.